Influence of environmental growth conditions on chalk yeasts causing bread spoilage. (August 2021) - Debonne, Els; Meuninck, Valentine; Vroman, Annemarie; Eeckhout, Mia
Abstract: The main objective of this study was the investigation of different environmental growth conditions on the growth of chalk yeasts, Hyphopichia burtonii (HB), Wickerhamomyces anomalus (WA) and Saccharomycopsis fibuligera (SF). Through multiple methods, including radial growth, biocontrol assay, growth/no-growth modelling and a bread challenge test, the influence of pH (4.5–6.5), temperature (22–30 °C), propionic acid (0–0.3%) and presence of other spoilage fungi was assessed. This study showed that pH and temperature does not play a major role on the growth of HB, WA and SF . Only WA shows optimal growth at pH 4.5 and 30 °C on MEA. The likeliness of growth is the following: HB > SF > WA, except from WA at pH 4.5/30 °C. Biocontrol activity was observed against Aspergillus niger and Penicillium paneum in the presence of high concentrations of HB at 30 °C. Furthermore, this study showed that HB is most sensitive to propionic acid (PA), followed by SF and WA . The effectiveness of PA was also shown through bread challenge tests. The following order of sensitivity against PA was observed: HB > SF > WA . Breads inoculated with WA had a shorter shelf-life (2–3 days less). Highlights: The influence of pH, temperature and propionic acid on chalk yeast growth was evaluated. The in-vitro results were validated in sourdough bread through a challenge test. Wickerhamomyces anomalus showed optimal growth at pH 4.5 and 30 °C. Hyphopichia burtonii exerted antifungal activity at 30 °C against Aspergillus niger and Penicillium paneum. Hyphopichia burtonii was most sensitive to propionic acid.